Treating people where they are: Nurse‐led micro‐elimination of hepatitis C in supported housing sites for networks of people who inject drugs in Victoria, Canada. Issue 5 (10th May 2022) - Selfridge, Marion; Barnett, Tamara; Lundgren, Karen; Guarasci, Kellie; Milne, Rozalyn; Drost, Anne; Fraser, Chris
Abstract: To achieve the World Health Organization's goal of eliminating hepatitis C (HCV) by 2030 requires enhanced HCV testing and treatment among people who use drugs (PWUD). Micro‐elimination of HCV is a strategy to target HCV testing and treatment efforts to specific segments of the population. From February to December 2018 nurses initiated a "seek & treat" micro‐elimination approach, increasing outreach and removing barriers to accessing HCV treatment in a clinic setting by testing and treating individuals, including PWUD, where they live. The aim of this study was to evaluate the proportion of clients with HCV antibodies and HCV RNA and the response to direct acting agent (DAA therapy) among people who live at or have social connections to local supportive housing sites through this nurse‐led micro‐elimination project in Victoria, Canada. A chart review of electronic medical records and case management documentation was used to collect relevant data of participants treated with DAA therapy, identified through specific housing site testing and outreach interventions. In total, 180 people were tested for HCV antibodies, 72 (40%) were antibody positive: 51 (28%) were RNA positive, 13 (7%) had spontaneously cleared and 8 (4%) had been previously treated. Of the 51 that were currently living with HCV, 43 people were started on treatment, 39 have achieved sustained virologic response (SVR). By providing treatment to clients in their homes and with their friends, clinicians have been able to treat clients, including those with limited contact with the health care system.